Adaptation in Arctic circumpolar communities: food and water security in a changing climate. Issue 1 (31st January 2016) - Berner, James; Brubaker, Michael; Revitch, Boris; Kreummel, Eva; Tcheripanoff, Moses; Bell, Jake
Abstract : The AMAP Human Health Assessment Group has developed different adaptation strategies through a long-term collaboration with all Arctic countries. Different adaptation strategies are discussed, with examples mainly from native population groups in Alaska.